Coping Strategies, Creativity, Social Self-Efficacy, and Hypercompetitiveness in Gambling Behaviors: A Study on Male Adolescent Regular Gamblers - Passanisi, Alessia; D’Urso, Giulio; Schimmenti, Adriano; Ruggieri, Stefano; Pace, Ugo (Frontiers in Psychology, 2020)
The aim of this study was to explore the cognitive and personality characteristics of male adolescent gamblers. Participants were 273 males in their teen age (M= 18.04, SD = 2.10) attending betting centers in Sicily, who completed self-report questionnaires on gambling, creativity, perceived social self-efficacy, hypercompetitiveness, and coping strategies. Pathological gamblers reported higher scores on avoidant coping strategies than occasional gamblers. They also scored higher on hypercompetitiveness than both occasional and problem gamblers. Further, problem gamblers scored higher than occasional gamblers on the complexity domain of creative personality. Furthermore, poor perceived social self-efficacy, higher levels of avoidant coping and hypercompetitiveness predicted pathological gambling. Theoretical, psycho-educational, and clinical implications are discussed.